The Impact of Aurora Supercomputer in Scientific Area and the Development Analysis - Okafor, Ngozi Lilian; Gunawan, Stella Putri; Zhafirah, Rafdah; Sujatmiko, Devlin Wen; Aldila, Amalia Shifa; Scantya, Miranti Andhita; Supriyono, Lawrence Adi; Putranto, Kartiko Eko (LPPM UNIKA Santo Thomas Medan, 2025)
Supercomputers are crucial in solving complex scientific and industrial computing due to its tremendous computational power in enabling large- scale simulations, scientific research, and advancement in various scientific fields. This study is conducted on Aurora supercomputer, a powerful exa-scale supercomputer designed for intricate computing tasks, such as climate modeling, intense simulations, and AI and machine learning. By making use of the literature review approach, we analyze the capabilities and impact of Aurora on the scientific environment. Our research suggests that Aurora is capable of significantly enhancing performance on processing data, surpassing supercomputers such as Frontier and Fugaku. Furthermore, we discuss Aurora's impact on driving groundbreaking research across multiple scientific domains and its real-world applications such as drug discovery driven by AI and machine learning. The result highlights that Aurora marked a remarkable milestone in revolutionizing computational research and further research can show the true power of the Aurora supercomputer